From Gratitude to Lamentation: On the Moral and Psychological Economy of Gift, Gain and Loss. (29th October 2014) - Carr, David
Abstract: The passing of Nelson Mandela and other figures of (diverse) contemporary importance may prompt the interesting question of how we might or should understand the psychological, social and moral function of lamentation in human life. This paper aims to show that such responses are not just of emotional and interpersonal significance, but also of serious moral import. To this end, the paper proceeds via exploration of conceptually and morally suggestive correspondences or resonances between the logical grammar of lamentation—which, to be sure, has received almost no latter day analytical attention—and that of gratitude or thankfulness in which there has been an enormous explosion of academic interest in recent years. The paper argues that there is no less case for a moral virtue of lamentation, than for a virtue of gratitude.